Properties of NaOH activated geopolymer with marble, travertine and volcanic tuff wastes. (30th November 2016) - Tekin, Ilker
Highlights: In this study, geopolymer composite material was produced without cement. Waste of marble and travertine was used to produce geopolimer composite material. Compressive strength of produced cast in place geopolymer composites were up to 46, 5 MPa with no heat curing. Tuff contained zeolite can be used as binder to produce geopolimer composites. Abstract: In this study, geopolymer composite pastes (GCM) were produced using wastes of marble, travertine and natural pozzolan, with 1 M, 5 M and 10 M NaOH as alkali-activator. Curing process were done at 20, 45 and 75 °C temperatures for 24 h in an oven. And after that GCMs were exposed to wet and dry condition separately. The strength tests were done on the 2nd, 3rd, 7th, 28th and 90th days of curing period. The compressive strengths of the specimens in the wet conditions were reduced depending on time, but in dry conditions were increased with curing time.